ROAD INFRASTRUCTURE AND SPATIAL ECONOMIC DEPENDENCE IN THE WESTERN REGION OF JAVA - Siti Herni Rochana; B. Kombaitan; Eka Purwanda (Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
The western region of the island of Java consists of three provinces, namely: West Java, Banten, and Jakarta, is a region that contributes significantly to the GDP of Indonesia. In 2010 the contribu-tion of the three provinces was 33.94% of the total GDP, and the remaining 66.06% came from the other 30 provinces. In spite of its high contribution, in terms of the value added by the western region of Java, there are inequalities between the regions. In the year 2010, Jakarta’s per capita income was ten times, or more, than that of Lebak. The existence of this problem in the income disparity between the regions in western Java raises questions relating to the spatial economic dependence of the west-ern region of Java. The unit analysis of the research is all the districts/cities in West Java, Banten, and Jakarta. The measurement used for the spatial economic dependence is Moran’s Index. Spatial varia-bles were comprised in the spatial weight matrix (matrix-W), which was formed using three approach-es: based on the distance, the neighbourhood, and the road transportation network. The economic variables in this study are the level of income per capita and economic growth. The results showed spatial economic dependence, based on distance and neighbourhood, tended to be low. Whereas, the spatial economic dependence based on road connectivity, especially freeways, showed a moderate correlation.Keywords: road infrastructure, spatial economic dependence, Moran’s Index, western region of Java.